Safety Net for India's Poor or Waste of Public Funds? Poverty and Welfare in the Wake of the World's Largest Job Guarantee Program - Stefan Klonner; Christian Oldiges (University of Heidelberg, Department of Economics, 2014)
This paper examines the effects of India's Mahatma Gandhi National Rural Employment Guarantee Act, currently the world's largest public employment program, on household consumption and poverty rates in rural India. Combining regionally coded data from consumption surveys with information on the district-wise rollout of the program, we employ a regression discontinuity design to estimate program effects during the years 2007 and 2008. We find large, season-specific effects among a traditionally deprived sub-group of the rural population, whose incomes are particularly dependent on agricultural wage labor. We find that for this group of households,which accounts for thirty percent of India's rural population, employment opportunities under the scheme have cut poverty during the agricultural lean season by as much as one half while we find no effect during the agricultural peak season. In a cost-benefit analysis we find that consumption increases among this group of households are of the same order of magnitude as the wage outlays of the program. We document that consumption among this group of households had previously exhibited severe systematic seasonal fluctuations and conclude that the employment program has had a lasting effect on consumption smoothing across agricultural seasons.
urn:nbn:de:bsz:16-heidok-168753
Keywords: 330; job guarantee; public employment programs; welfare programs; poverty; consumption smoothing; India